PEMANFAATAN TEKNOLOGI INFORMASI UNTUK MENINGKATKAN PENJUALAN DAN PEMASARAN PRODUK OLAHAN SAYUR KELOMPOK TANI DESA SAMIRAN, KECAMATAN SELO, KABUPATEN BOYOLALI - Desy Amalia Candrakusumah; Doni Mardiyanto; Ambyah Atas Aji (FAKULTAS EKONOMI UNIVERSITAS SURAKARTA, 2023)
Abstract The innovation produced by the community of Samiran Village, Selo, Boyolali Regency by processing vegetables into vegetable chips provides high economic opportunities for the community. Vegetable chips produced by farmer groups are currently only sold in the Boyolali area. So that vegetable chips can be known more widely and generate higher income, the author is motivated to carry out community service activities. This activity was carried out with the aim of motivating farmer groups to be able to sell and market using social media. In addition, this activity provides knowledge to farmer groups on how to use social media so that they can increase sales and do marketing properly. The implementation method used in this activity is a workshop on the importance of using social media and how to use social media to support marketing and product sales. The activity was carried out smoothly. All participants participated in the workshop activities by actively asking questions and following all directions and procedures for making social media well. Suggestions for further community service activities are to conduct periodic reviews in order to monitor the promotion and sales process of vegetable chips and provide additional material related to how to create content that can attract consumers to buy vegetable chips. Keywords: Information Technology, Sales, Marketing, Processed Vegetable, Samiran Village